Diurnal and seasonal trends and source apportionment of redox-active metals in Los Angeles using a novel online metal monitor and Positive Matrix Factorization (PMF). (February 2018) - Mousavi, Amirhosein; Sowlat, Mohammad H.; Sioutas, Constantinos
Abstract: In the present study, we identified the sources of four redox-active metals, including Iron (Fe), Chromium (Cr), Cupper (Cu), and Manganese (Mn) and quantified the contribution of these sources to PM2.5 concentrations in central Los Angeles, California, by employing time-resolved measurements (i.e., a time resolution of 2 h) with a recently developed online metal monitor and Positive Matrix Factorization (PMF). Size distribution of ambient PM (14 nm–10 μm) was measured using the Scanning Mobility Particle Sizer (SMPS) and Optical Particle Sizer (OPS). Auxiliary variables were also collected, including elemental (EC) and organic carbon (OC), gaseous pollutants (NO2 and O3 ), meteorological parameters (including relative humidity (RH) and temperature), and traffic data (for heavy- (HDVs) and light-duty vehicles (LDVs)). A 4-factor solution was found to be optimum for the chemically-speciated dataset, whereas a 5-factor solution appeared to be most plausible for the size distribution data. The factors included fresh traffic, soil/road dust, urban background aerosol, secondary aerosol, and nucleation (only resolved for the size distribution data). Fresh traffic was the major contributor to Fe and Cu concentrations, whereas Cr was mostly found in the urban background aerosol (reflecting a mixture of small local sources as well as aged traffic emissions), and Mn mostly came from both soil/road dust and was to a lesser degree found in urban background aerosol. Secondary aerosol did not contribute to the concentrations of any of these metals, but was associated with very high loading of OC, as expected. Even though the urban background aerosol and secondary aerosol appeared to be characterized by "aged" particles and have a rather homogeneous spatial distribution, the reactions and processes involved in their formation are entirely different. Our results provide insights into the sources of redox-active metals in central Los Angeles. They also underscore the benefits of novel measurement techniques for PM-bound metals, which could enhance our understanding of the sources of atmospheric aerosols by providing us with measurements with finer time resolutions that otherwise would not have been possible using traditional filter-based measurement techniques. Highlights: A novel metal monitor was used for online measurement of redox-active metals. PMF model was used for source apportionment of these metals in central Los Angeles. Factors were traffic, urban background aerosol, secondary aerosol, and soil/road dust. Traffic and soil/road dust were the main contributors to Fe, Mn, and Cu concentrations. Urban background aerosol was the main contributor to Cr concentrations.